Pembiasaan Shalat Berjama’ah dalam Membentuk Karakter Santri di Pondok Pesantren Al-Mu’arif Al-Mubarok Patrang Jember - Khairi, Khairi; Saihan, Saihan; Mislikhah, St. (IJIT: Indonesian Journal of Islamic Teaching, 2025)
Education is one of the important things in the life of every toam. Education aims not only to form humans who are intelligent in their brains and skilled in carrying out tasks, but are expected to produce humans who have morals. Therefore, education is used as a tool in shaping and fostering one's attitude and mentality. is the most important education to be taught to a child, especially children at the age of du, either taught in schools or in Islamic boarding schools. describe and analyze the habit of praying in congregation in shaping the character of students in the Al-Mu'arif Al-Mubarok Islamic boarding school. Research methods used. is a qualitative approach with a case study type. The results of the research show: in shaping religious character, independent character, and mutual cooperation character through the habit of praying in congregation and with the guidelines in Islamic boarding schools, namely, forced, forced, ordinary, accustomed and extraordinary where in the end it will form a good character and become a noble character. Keyword: Habituation, Salat Congregation, Foration Character Students